Biological studies of clavine alkaloids targeting CNS receptors - Tasker, Nikhil R.; Pazur, Ethan J.; Wipf, Peter (Frontiers in Psychiatry, 2023)
In contrast to well established psychedelics such as lysergic acid diethylamide (LSD) and psilocybin, ergot alkaloids of the clavine subclass have not been thoroughly investigated, in spite of their broad occurrence in nature and their well-established potent physiological effects. This study presents the current knowledge on the biological properties of clavine alkaloids, draws comparisons to the pharmacology of ergolines and related psychedelics, and demonstrates opportunities to develop novel structure-activity relationship (SAR) profiles. The latter could usher in a new stage of medicinal chemistry studies that enable an expansion of the currently structurally limited portfolio of psychedelic therapeutics.